Profil' mezhdupolusharnoi asimmetrii i dvigatel'nye kachestva - Berdichevskaya, E. M. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to reveal the peculiarities of motor qualities with lateral phenotype. The influence of a brain interhemispheric asymmetry's profile on power and speed physical qualities had been investigated according positions of an individual -typological approach, taking into consideration the sight's dominant side, and the upper extremities' motorics. The asymmetry in the majority of hextral and symmestral characteristics, the specific of motorical portrait and correlation interconnections of its elements in objects with the unilateral left and right lateral phenotype had been revealed.